LENGTH-WEIGHT RELATIONSHIP AND RELATIVE CONDITION IN OMPOK BIMACULATUS (BLOCK) FROM BHAVANISAGAR RESERVOIR (TAMIL NADU) - Sivakami, S (Indian Journal of Fisheries, 2011)
Length-weight relationship and relative condition in Ompok bimaculatus were studied. Analysis of covariance of the regressions for the two sexes showed no significant difference in slopes. The value of the exponent indicated a deviation from the cube law. The point of inflexion in the relative condition plotted on a lengthwise basis gave the size at first maturity, especially in males. Seasonal variations in the condition was found to be influenced by the spawning cycle.